Legume Genetics and Biology From Mendel's Pea to Legume Genomics - Smýkal, Petr; Bishop von Wettberg, Eric J.; McPhee, Kevin (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Legumes have played an important part as human food and animal feed in cropping systems since the dawn of agriculture. The legume family is arguably one of the most abundantly domesticated crop plant families. Their ability to symbiotically fix nitrogen and improve soil fertility has been rewarded since antiquity and makes them a key protein source. Pea was the original model organism used in Mendel´s discovery of the laws of inheritance, making it the foundation of modern plant genetics. This book based on Special Issue provides up-to-date information on legume biology, genetic advances, and the legacy of Mendel.